Transient Stability Boundary Assessment Using Rate of Change Kinetic Energy (RACKE) Method for Optimizes Critical Clearing Time - Jabbar Mohammed, Inas (International Journal of Engineering and Technology, 2018)
In this paper the Rate of Change Kinetic Energy (RACKE) method for multi machine systems was studied and applied to determine of Transient Stability Boundary (TSB) of critically disturbed machine for given contingency. The method has been tested on Iraqi national grid system 400KV. The  obtained results were compared by (TSB) assessment based on the Rate of Change Kinetic Energy (RACKE)method  with benchmark result (conventional method) through the critical clearing time CCT and the absorbed time for knowing the system case stable or unstable for limiting disturbance conditions. The simulation results show that the method can provide reliable, precise, and quite information about the transient stability boundary.